Making Rosella Flower Syrup (Hibiscus sabdariffa L.) with Cinnamon (Cinnamomum burmannii) - Ramadhanti, Debi D; Priyanto, Bambang; Rahmi, Ainu (Universitas Pattimura, 2023)
This study aimed to determine the exact cinnamon concentration in the manufacture of rosella flower petal syrup based on its physical and chemical properties. A completely randomized experimental design with six levels of cinnamon concentration, i.e., 0, 1, 3, 5, 7, and 9 g, respectively, replicated four times was applied in this research. Analyses were performed on both the concentrated and diluted forms of the syrup. Parameters observed were sensory tests (aroma, taste, and color), physical tests on viscosity, and chemical tests (sugar content, pH, and vitamin C). Observation parameters include organoleptic tests (color, taste, and aroma) by untrained panelists, viscosity using a digital viscometer, chemical tests of sugar content on a refractometer, pH on a pH meter, and vitamin C using an iodometric method. Observational data were analyzed using the analysis of variance. If the value of the F-table is significant then followed by Duncan's New multiple range test (α = 0.05) and Friedman analysis for sensory tests. The exact concentration of the addition of cinnamon in making rosella flower petal syrup was 9 g (K6) based on sensory parameters (taste) with a mean rank of 17,84, viscosity/thickness of 46,325 cP, based on the results of the De Garmo effectiveness index test, the pH of the concentrated syrup was 3,350 and the pH of the diluted syrup was 3,625; the sugar content of the concentrated syrup was 66,75°brix.